Utilizing of alkybenzene homologous series on the determination of kovats retention index in the RP-HPLC using methanol/water solvent system - Rinaldi Idroes (Indonesian Journal of Pharmacy, 2009)
Retention times in high performance liquid chromatography are very susceptible to small changes of the stationary phase, temperature, pH-value, mobile-phase composition and flow rate. One of the methods to minimize theseeffects is by utilizing a retention index system. In contrast to GC, the retention Index determination method in HPLC is still widely discussed, because of difficulty utilizing n-alkane as standard. In addition, the solutes in HPLC interact with the mobile-phase, thus the retention data also depend on the mobilephase. It is not easy to use n-alkane in HPLC as standards because of considerable problems. Due to their very non polar properties, hence in most reversed phase systems, they show large retention times. Therefore, using nalkane in routine analysis could be inconvenient. In comparison with n-alkane, the alkylbenzene homologous series are stable compound and commercially available. They have a high UV absorbance at the wavelength of 254 nm, and thus are easily detected by a UV detector. This paper will introduce Kovats Retention Index Determination in the HPLC by using alkylbenzene homologous series and then is to be connected with n-alkane as a frame of reference. Steroids were used as test substance for determining Kovats retention index values in methanol/ water system.Key words: RP-HPLC, Kovats Retention Index, n-Alkane, Alkyl Benzene.